PSYCHOSOCIAL ILLNESS IN CHILDREN WITH THALASSEMIA: A CASE-CONTROL STUDY - Afzal, Erum; Sheikh, Muhammad Aslam; Bhaba, Sajjad Hussain; Ahmed, Tanveer; Iqbal, Imran; Iqbal, Muhammad Khalid (Journal of Rawalpindi Medical College, 2023)
INTRODUCTION: Thalassemia is the most common hemolytic autosomal recessive disorder. Pakistan has significant number of thalassemic children .The children with chronic disorders like thalassemia are prone to develop psychosocial illness including depression, anxiety, intellectual and behavioral issues. OBJECTIVE: To assess the psychosocial illness in children with thalassemia and to compare these problems in children with and without Thalassemia PLACE & DURATION: The Children’s Hospital and the institute of child health, Multan. From January to September 2021. STUDY DESIGN: Case-control MATERIAL AND METHOD: In this study 50 children with Thalassemia and 50 normal children were enrolled as case & control according to inclusion and exclusion criteria. After approval from institutional ethical committee, detailed history ,Socioeconomic status, educational status of parent and child, age of diagnosis of disease, and whether thalassemia is well controlled or not and complications were noted. A Pediatric Symptom Checklist was used for psychosocial problems in all children. Data was analyzed by using SPSS version 22. Mean and standard deviation for quantitative data, while frequencies and percent for qualitative data was calculated. P-value was calculated by Chi square test. Prevalence ratio (ODDS ratio) with 95%confidence interval of all variables were calculated. RESULTS: Out of 100 patients 50 were in case group (Thalassemia) and 50 control (non-thalassemic.Male female ratio was 1.2:1. 60 %( n=30) cases, 78 %( n=39) control patients were age ranges between 5 to 10 years. Educational level of parents of 40%(n=20),and 56%(n=28) was below matric,42%(n=21) and 90%(n=45) patients were going to school in case and control group respectively.82%(n=41) patients belonged to low socioeconomical status in each group. Regarding characteristics of thalassemia 74 %( n=37) patients were diagnosed within 1st year of life, while 26 %( n=13) after 1st year.64 %( n=32) had well controlled and 36 %( n=18) poor controlled disease. 20%(n=10) had developed Diabetes mellitus,2%(n=1) heart failure,74%(37) growth failure,76%(n=38) hemolytic facial features and 72%(n=36)skin discoloration. Psychosocial problems were statistically significant in children with Thalassemia as compared to healthy ones (p-value<0.001).Poorly controlled thalassemia and complications of heart and growth failure were found statistically significant risk factors. CONCLUSION: Psychosocial problems are common in children with thalassemia as compared to healthy ones. So these patients must be referred for detailed psychological evaluation and management along with medical treatment.